PEMETAAN PROFIL PASIEN/KLIEN RUMAH SAKIT UMUM DAERAH (RSUD) KOTA X MENGGUNAKAN NET PROMOTER SCORE - Elsa Roselina (Jurnal Vokasi Indonesia, 2016)
Regional General Hospital City X is the only government-owned hospitals of city X, had some visionincluding provide excellent service quality plenary to the whole society. Net Promoter Score (NPS) is atool and concept of customer satisfaction, which through NPS companies can see their performanceaccording to the customer's perspective. This study aimed to obtain consumer profiles and identifystrengths and weaknesses in the service of the Regional General Hospital City X based on the perceptionof consumers. This study used a quantitative approach with survey method. Data captured in one shootmeasurement from August until September 2015. Instruments used in the form of a questionnaire. Theresearch subjects were patients/families undergoing outpatient treatment or hospitalization in sometreatment rooms of the Regional General Hospital City X. The total sample was 442 persons, calculatedusing the Slovin formula with alpha 0.05. The analysis was univariate analysis. The final resultsshowed the profile of patients/families mostly as consumers detractors (45.2%) than consumers promoters(19.7%), where the value indicated by the NPS better perception of inpatients than outpatients.Weakness in outpatient services is a long queue system and the limited facilities, whereas in inpatientfacilities are limited and hygiene problems. City Hospital X strength in providing services is thefriendliness of its officers (doctors, nurses, administration).Keywords: net promoter score, consumer profile, hospital service